AN OVERVIEW OF FUTURE CLIMATE-FORCED MIGRATION IN INDONESIAN URBAN COASTAL AREAS (Case Study: Semarang City ) - Rukuh Setiadi; Kunarso Kunarso; Rizki Kirana Yuniarti (Jurnal Kajian Pengembangan Perkotaan, 2012)
Climate change leading to the global sea level rise has resulted in serious impact to physical and social life in urban coastal areas. Community and government in the coastal areas of Semarang City have taken some measures to deal with the sea level rise, from adaptation to protection actions. This paper will show patterns and characteristics of the future climate-forced migration. The data were collected from 300 respondents, who are currently living in coastal and urban areas settlement of Semarang, which potential to have impact from the sea level rise in the near, mid, and a more distant future. This paper discusses some consequences of this projected phenomenon and suggests some urban policy implications.